2021
DOI: 10.1021/acssuschemeng.1c01674
|View full text |Cite
|
Sign up to set email alerts
|

Designing Low-Viscosity Deep Eutectic Solvents with Multiple Weak-Acidic Groups for Ammonia Separation

Abstract: Developing NH 3 separation technology with high efficiency is very meaningful for the advancement of the NH 3 synthesis process. In this work, a new class of deep eutectic solvents (DESs) were designed by pairing N,N,N′,N′-tetramethyl-1,3-propanediamine dihydrochloride ([TMPDA]Cl 2 ) with phenol (PhOH) at the molar ratios of 1:3∼7. [TMPDA]Cl 2 + PhOH DESs have multiple weak-acidic groups and viscosities of as low as 48.1 cP at 298.2 K. They also exhibit excellent performance for the separation of NH 3 , showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
“…The densities and viscosities data of liquid absorbent are fundamental physical properties for the devise of gas absorption process. [22][23][24] As shown in Figure 1 1) and (2), 25,26 respectively.…”
Section: Physical Propertiesmentioning
confidence: 82%
“…The densities and viscosities data of liquid absorbent are fundamental physical properties for the devise of gas absorption process 22–24 . As shown in Figure 1, the densities and viscosities values of three cuprous‐based composites ILs at 293.15–353.15 K. The sequence of density was as follows: [EimH][OAc]–0.7CuOAc > [EimH][OAc]–0.6CuOAc > [EimH][OAc]–0.5CuOAc.…”
Section: Resultsmentioning
confidence: 99%
“…Ionic liquids (ILs) have shown promising application in gas separation given the wide liquid range, extremely low volatility and unlimited motif choices of them 19–27 . Within this regard, it is necessary to obtain ILs with high capacity and excellent reversibility for gas absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) have shown promising application in gas separation given the wide liquid range, extremely low volatility and unlimited motif choices of them. [19][20][21][22][23][24][25][26][27] Within this regard, it is necessary to obtain ILs with high capacity and excellent reversibility for gas absorption. To achieve this goal, introducing multiple-site reversible chemical absorption is an effective strategy.…”
mentioning
confidence: 99%